Power system economics designing markets for electricity - Stoft, Steven (IEEE Press, 2002)
The book reveals for the first time how uncoordinated regulatory and engineering policies cause boom-bust investment swings and provides guidance and tools for fixing broken markets. It also takes a provocative look at the operation of pools and power exchanges.